Fundamentos y consideraciones generales sobre restauración ecológica para Colombia (2016)
Colombia has been is undergoing a process of rapid ecosystem deterioration that has affected, at different scales, the provision of strategic ecosystem services to rural and urban populations. This situation has led to the need for academics, policy makers, and our local communities to consider various integrated strategies of ecosystem conservation such as the reinforcement of novel and existing protected areas, changing land use and certainly, the restoration of ecosystems that provide strategic services. However, the conceptual and methodological framework of ecological restoration in the country today is significantly dispersed at every level, even within the SINA (Sistema Nacional Ambiental). The purpose of this working paper is to introduce the most important concepts related to ecological restoration in order to have a standardized institutional vision that may generate a space for the discussion and application of this issue in the institutional programs, lines of work and emphasis of researchers.